EMPOWERING WOMEN THROUGH POLITICAL EDUCATION FOR HOUSEWIVES IN SERDANG BEDAGAI REGENCY - Evi Novida Ginting Manik; Mohammad Ridwan (Academic Solution Publisher, 2025)
On a daily basis, women often find themselves in a disadvantaged position within the political sphere. Several factors contribute to this condition, one of which is the limited access to and mastery of political knowledge. This program is designed to empower women through political education that focuses on strengthening their understanding, capacity, and confidence to actively participate in decision-making processes. Women’s political participation continues to face structural and cultural barriers, including restricted access to information, low self-confidence, and the persistent influence of patriarchy. To overcome these challenges, the program organizes interactive political education forums that encourage participants to understand their political rights, analyze social issues, and enhance political skills to become more empowered in voicing their aspirations. As a strategic effort, the program partners with the General Elections Commission (KPU) of Serdang Bedagai to ensure that the educational content is relevant to women’s needs while also improving program effectiveness through expert involvement and broader access to information. Through gender-based political education, this program is expected to encourage women to participate more actively in democratic processes, strengthen their position in policymaking, and contribute to the creation of a more inclusive and equitable society